Human parvovirus B19 frequency among blood donors after an epidemic outbreak: relevance of the epidemiological scenario for transfusion medicine - Adamo, Maria Pilar (2020)
A retrospective, cross-sectional study was conducted to determine the frequency of human parvovirus B19 (B19V) infected individuals, viral loads and immunity among blood donors from Argentina, in a post-epidemic outbreak period. B19V DNA and specific IgG were tested in minimum study samples of donors attending a blood bank at Córdoba, Argentina, in 2014. Anti-B19V IgM and viral loads were determined in B19V-positive plasma samples. Seven of 731 samples (0.96%) resulted positive, corresponding to individuals aged 32–53 years, four of them repeat donnors and three first-time donors. Viral loads were <103 IU/mL. None had IgM and 6/7 had IgG, one of them at a high level (in the range of 100–200 IU/ml, and the remaining 5 at low to medium level, 5–50 IU/ml). Thus one case was classified as acute infection (DNA+/IgM-/IgG-) and six as potentially persistent infections (DNA+/IgM-/IgG+). No coinfections with other pathogens of mandatory control in the pre-transfusion screening were detected. Prevalence of IgG was 77.9% (279/358). This study provides the first data of B19V prevalence in blood donors in Argentina, demonstrating high rates of acute and persistent B19V infections and high prevalence of anti-B19V IgG in a post-epidemic period. Further research is needed to elucidate mechanisms/factors for B19V persistence as well as follow-up of recipients in the context of haemo-surveillance programs, contributing to the knowledge of B19V and blood transfusion safety.